Uji Efektivitas Ekstrak Daun Trembesi (Samanea saman (Jacq.) Merr) Untuk Menghambat Pertubuhan Jamur Colletotrichum sp. Penyebab Penyakit Antraknosa Pada Pepaya (Carica Papaya) - PINEM, ALPIN JUAN HAGATA; SUPRAPTA, DEWA NGURAH; SUNITI, NI WAYAN (Agrotrop : Journal on Agriculture Science, 2023)
Effectiveness of Rain Tree Leaf Extract ( Samanea Saman (Jacq.) Merr) to Inhibit the Growth of the Fungus Colletotrichum sp. the Cause of Anthracnose Disease on Papaya ( Carica papaya ) . Due to its high nutritional value and high economic value, papaya is a local fruit that is in great demand in the community. The production of papaya fruit fluctuates due to a number of factors, one of which is the fungus Colletotrichum sp., which causes anthracnose disease in papaya fruit. In most cases, synthetic fungicides are utilized to combat anthracnose. Reduce the use of synthetic fungicides and replace them with more environmentally friendly plant-based fungicides, such as those derived from plant extracts. This study aimed to determine the efficacy of rain tree ( Samanea saman ) leaf extract in inhibiting and controlling the growth of the anthracnose-causing fungus Colletotrichum sp. in papaya fruit. In vitro and in vivo evaluation of the efficacy of trembesi leaf extract against the fungus Colletotrichum sp. The minimum inhibitory concentration (MIC) of trembesi leaf extract to inhibit the growth of Colletotrichum sp. was determined to be 0,1%. The results of the colony test demonstrated that the trembesi leaf extract inhibited the growth of Colletotrichum sp. colonies. In vivo inhibition tests revealed that trembesi leaf extract could inhibit the growth of fungal colonies, prevent infection, and suppress the growth of Colletotrichum sp. The 2,5% extract concentration can prevent 66,22% of the damage caused by Colletotrichum sp. to papaya fruit.